PERTIMBANGAN HAKIM DALAM PEMIDANAAN PELAKU PEMBUAT IKLAN PERUSAHAANDI INTERNET TANPA IZIN - Etieli Buulolo (LPPM Universitas Nias Raya, 2024)
The crime of creating illegal business advertisements on the Internet is the crime of taking advantage of another person's business position to deceive people via the Internet. Decision No. 819/Pid.Sus/2016/PN. Jmb is one of the decisions regarding the conduct of corporate advertising without permission on the Internet. This study uses a type of normative legal research with a legal approach, a case approach, a comparative approach and an analytical approach. Based on the research results and discussion, we can conclude. Based on research findings and discussion, it can be concluded that the judge's considerations in decision number 819/Pid.Sus/2016/PN. Jmb in the conviction of perpetrators who create company advertisements on the internet without permission must be proven in accordance with Article 184 of the Criminal Procedure Code and also based on proven facts in the trial and has fulfilled the elements of Article 35 of Law Number 11 of 2008 concerning Electronic Transaction Information, so that the panel of judges believes that the defendant has been legally and convincingly proven guilty of committing the criminal act for which he was charged, namely